2005
DOI: 10.1177/1043659604270978
|View full text |Cite
|
Sign up to set email alerts
|

Academic-Community Partnerships: Opening the Doors to a Nursing Career

Abstract: With the belief that diversity is strength, the community of Reading, Pennsylvania, set forth an effort to meet the challenges of the disparity within the local nursing workforce with a comprehensive, long-term approach for the recruitment and retention of an underrepresented group. An academic-community partnership was formed to develop multifaceted programs and support across school and community agency systems. The Alvernia College Nursing Department has taken a leadership role to coordinate many community … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…One innovative strategy to influence early professional socialization and pre-entry IPE could take place through summer camps for junior high and high school students. Summer camp experiences can provide an opportunity to enhance understanding of a career in healthcare and are a socialization strategy growing in popularity in medicine and nursing (Thacker, 2005). Moreover, interprofessional camps, with curriculum focused on health professions broadly can provide specific information on the roles and responsibilities of the entire health care team, in a way that emphasizes the benefits of collaboration to patient outcomes.…”
Section: Discussionmentioning
confidence: 96%
“…One innovative strategy to influence early professional socialization and pre-entry IPE could take place through summer camps for junior high and high school students. Summer camp experiences can provide an opportunity to enhance understanding of a career in healthcare and are a socialization strategy growing in popularity in medicine and nursing (Thacker, 2005). Moreover, interprofessional camps, with curriculum focused on health professions broadly can provide specific information on the roles and responsibilities of the entire health care team, in a way that emphasizes the benefits of collaboration to patient outcomes.…”
Section: Discussionmentioning
confidence: 96%
“…Buchan (2007) reported that with the increased need for nurses in the UK, particularly after 2001, an increasing number of nurses would be accepted who had entered the profession outside the country. A similar situation is present in the United States (Thacker 2005). For this reason, nurse recruitment and retention strategies by developed foreign countries, like the US and the UK, are likely to be having an effect on nursing students' career planning in the profession.…”
Section: Discussionmentioning
confidence: 80%
“…Hispanic students capable of meeting the demand for bilingual nurses are underrepresented in college science and nursing programs and face a number of important challenges to their success (Fry, 2002;Gasbarra & Johnson, 2008;Velez-McEvoy, 2010). Thacker (2005) has called for a "comprehensive, long-term approach for the recruitment and retention of Hispanic nurses" (p. 57), which can be answered with college-level nurse education programs capable of identifying and recruiting appropriate students. Nurse education programs that can address these challenges have the potential for graduating Hispanic students with the knowledge, skills, and language abilities needed to meet the strong demand for bilingual nurses.…”
Section: Spanish and Englishmentioning
confidence: 99%
“…Nurse education programs that can address these challenges have the potential for graduating Hispanic students with the knowledge, skills, and language abilities needed to meet the strong demand for bilingual nurses. Many community colleges are meeting the urgent need for nurses by creating and expanding nursing programs, sometimes with financial, instructional, or logistical help from local health care organizations (Curtis & West, 1992;Thacker). Such programs are most likely to succeed if academic strengths of Hispanic students are recognized and supported (e.g., encouraging cooperative and student-centered activities), while challenges such as low science and math skills are addressed by program components (e.g., specialized workshops or classes) (Drane, Smith, Light, Pinto, & Swarat, 2005).…”
Section: Spanish and Englishmentioning
confidence: 99%